Está en la página 1de 14

# Table of Basic Integrals

Basic Forms
Z
(1)

xn dx =

Z
(2)

1
xn+1 , n 6= 1
n+1
1
dx = ln |x|
x

Z
udv = uv

(3)

vdu

1
1
dx = ln |ax + b|
ax + b
a

(4)

Z

1
1
dx =
2
(x + a)
x+a

(5)

Z
(6)

Z
(7)

(x + a)n+1
, n 6= 1
(x + a) dx =
n+1
n

x(x + a)n dx =

Z
(8)

Z
(9)

## (x + a)n+1 ((n + 1)x a)

(n + 1)(n + 2)

1
dx = tan1 x
1 + x2

1
1
1 x
dx
=
tan
a2 + x 2
a
a
1

Z
(10)

a2

x2
x
dx = x a tan1
2
2
a +x
a

Z
(11)

x3
1 2 1 2
x a ln |a2 + x2 |
dx
=
a2 + x 2
2
2

Z
(12)

Z
(13)

1
2
1 2ax + b

tan
dx
=
ax2 + bx + c
4ac b2
4ac b2
Z

(14)

1
a+x
1
dx =
ln
, a 6= b
(x + a)(x + b)
ba b+x
Z

(15)

Z
(16)

ax2

x
1
dx = ln |a2 + x2 |
2
+x
2

a
x
dx =
+ ln |a + x|
2
(x + a)
a+x

x
1
b
2ax + b
dx =
ln |ax2 +bx+c|
tan1
+ bx + c
2a
a 4ac b2
4ac b2

## Integrals with Roots

Z
(17)

Z
(18)

Z
(19)

2
x a dx = (x a)3/2
3

1
dx = 2 x a
xa

1
dx = 2 a x
ax
2

x x a dx =

(20)

(21)

Z
(22)

Z
(23)

Z r
(24)

Z
(26)
(27)
Z p

(28)
Z p

(29)


ax + b dx =

2b 2x
+
3a
3

(ax + b)3/2 dx =

or
or

ax + b

2
(ax + b)5/2
5a

x
2

dx = (x 2a) x a
3
xa

p
x
dx = x(a x) a tan1
ax

Z r
(25)

2a
(x a)3/2 + 25 (x a)5/2 ,
3
4
2
x(x a)3/2 15
(x a)5/2 ,
3
2
(2a + 3x)(x a)3/2
15

p
x(a x)
xa

p



x
dx = x(a + x) a ln x + x + a
a+x

x ax + b dx =

x(ax + b) dx =

2
2
2 2
(2b
+
abx
+
3a
x
)
ax + b
15a2

i
p
p
1 h

2
(2ax
+
b)
ax(ax
+
b)

b
ln
a
x
+
a(ax
+
b)

3/2
4a



2
p
p
b
b
x
b3

3
3
x (ax + b) dx =
2 +
x (ax + b)+ 5/2 ln a x + a(ax + b)
12a 8a x 3
8a


1
1

x2 a2 dx = x x2 a2 a2 ln x + x2 a2
2
2
3

Z
1
1
x
a2 x2 dx = x a2 x2 + a2 tan1
2
2
a2 x 2

(30)

Z
(31)

Z
(32)

3/2
1 2
x a2
x x2 a2 dx =
3

1

dx = ln x + x2 a2
x 2 a2
Z

(33)

Z
(34)

Z
(35)

Z
(36)

(37)
Z

ax2

a2

1
x
dx = sin1
2
a
x

x
dx = x2 a2
x 2 a2

x
dx = a2 x2
a2 x 2

1
x2
1

dx = x x2 a2 a2 ln x + x2 a2
2
2
x 2 a2

p
b + 2ax 2
4ac b2

2
+
ln 2ax + b + 2 a(ax + bx c)
+ bx + c dx =
ax + bx + c+
3/2
4a
8a

(38)
Z

1  2
2
2
2
a
ax
+
bx
+
c
3b
+
2abx
+
8a(c
+
ax
)
x ax2 + bx + c dx =
48a5/2



+3(b3 4abc) ln b + 2ax + 2 a ax2 + bx + c
4

Z
(39)

(40)
Z

p
1
1

dx = ln 2ax + b + 2 a(ax2 + bx + c)
2
a
ax + bx + c

p
x
1 2
b

2
dx =
ax + bx + c 3/2 ln 2ax + b + 2 a(ax + bx + c)
2
a
2a
ax + bx + c
Z

(41)

dx
x

=
(a2 + x2 )3/2
a2 a2 + x 2

## Integrals with Logarithms

Z
ln ax dx = x ln ax x

(42)

x2
1
x ln x dx = x2 ln x
2
4

1 3
x3
x ln x dx = x ln x
3
9

(43)

(44)

Z
(45)

x ln x dx = x

ln x
1

n + 1 (n + 1)2

ln ax
1
dx = (ln ax)2
x
2

ln x
1 ln x
dx =
2
x
x
x

(46)

(47)

n+1


,

n 6= 1

Z
(48)

Z
(49)

Z
(50)



b
ln(ax + b) dx = x +
ln(ax + b) x, a 6= 0
a

## ln(x2 + a2 ) dx = x ln(x2 + a2 ) + 2a tan1

ln(x2 a2 ) dx = x ln(x2 a2 ) + a ln

x
2x
a

x+a
2x
xa

(51)


Z


1
b
2
1 2ax + b
2
ln ax + bx + c dx =
4ac b tan
2x+
+ x ln ax2 + bx + c
a
2a
4ac b2
Z
(52)

bx 1 2 1
x ln(ax + b) dx =
x +
2a 4
2

Z
(53)

x ln a b x

Z
(54)

Z
(55)

1
1
dx = x2 +
2
2




a2
2
x 2 ln a2 b2 x2
b

## (ln x)3 dx = 6x + x(ln x)3 3x(ln x)2 + 6x ln x

Z
(56)

Z
(57)

2 2



b2
2
x 2 ln(ax + b)
a

x(ln x)2 dx =

x2 1 2
1
+ x (ln x)2 x2 ln x
4
2
2

x2 (ln x)2 dx =

2x3 1 3
2
+ x (ln x)2 x3 ln x
27
3
9
6

## Integrals with Exponentials

Z
(58)
(59)
Z

ax

xe

Z x

1 ax
i
2
2
et dt
dx =
xe + 3/2 erf i ax , where erf(x) =
a
2a
0
Z

xex dx = (x 1)ex

(60)

ax

(61)

xe

Z
(63)

(64)

Z
(65)

(66)

2 ax

xe

x e

n ax

eax


dx =

2
x2 2x
2 + 3
a
a
a

eax

xn eax n
dx =

a
a

xn1 eax dx

(1)n
dx = n+1 [1 + n, ax], where (a, x) =
a
Z

(67)

dx =

x
1
2
a a


x3 ex dx = x3 3x2 + 6x 6 ex

x e

n ax


x2 ex dx = x2 2x + 2 ex

(62)

1
eax dx = eax
a

ax2


i
dx = erf ix a
2 a
7

Z
x

ta1 et dt

ax2

(68)

xeax dx =

(69)

Z
(70)

dx = erf x a
2 a

1
dx =
4

2 ax2

xe

1 ax2
e
2a

2
a) eax
erf(x
3
a
2a

## Integrals with Trigonometric Functions

Z
(71)

Z
(72)

(74)

sin2 ax dx =

sin3 ax dx =

(73)

1
sin ax dx = cos ax
a
x sin 2ax

2
4a

## 3 cos ax cos 3ax

+
4a
12a



1
1 1n 3
2
sin ax dx = cos ax 2 F1 ,
, , cos ax
a
2
2
2
n

Z
(75)

cos ax dx =

Z
(76)

Z
(77)

cos2 ax dx =

cos3 axdx =

1
sin ax
a

x sin 2ax
+
2
4a

## 3 sin ax sin 3ax

+
4a
12a
8

Z
(78)



1+p 1 3+p
1
1+p
2
cos ax 2 F1
, ,
, cos ax
cos axdx =
a(1 + p)
2 2 2
p

Z
(79)

cos x sin x dx =

1 2
1
1
sin x + c1 = cos2 x + c2 = cos 2x + c3
2
2
4

Z
(80)

cos ax sin bx dx =

Z
(81)

sin2 ax cos bx dx =

Z
(82)

Z
(83)

## cos[(a b)x] cos[(a + b)x]

, a 6= b
2(a b)
2(a + b)

sin2 x cos x dx =

cos2 ax sin bx dx =

Z
(84)

+

4(2a b)
2b
4(2a + b)
1 3
sin x
3

## cos[(2a b)x] cos bx cos[(2a + b)x]

4(2a b)
2b
4(2a + b)

cos2 ax sin ax dx =

1
cos3 ax
3a

(85)
Z
x sin 2ax sin[2(a b)x] sin 2bx sin[2(a + b)x]
sin2 ax cos2 bxdx =

4
8a
16(a b)
8b
16(a + b)
Z
(86)

sin2 ax cos2 ax dx =

Z
(87)

x sin 4ax

8
32a

1
tan ax dx = ln cos ax
a
9

tan2 ax dx = x +

(88)

Z
(89)

tann+1 ax
tan ax dx =
2 F1
a(1 + n)
n

Z
(90)

tan3 axdx =

1
tan ax
a

n+1
n+3
, 1,
, tan2 ax
2
2

1
1
ln cos ax +
sec2 ax
a
2a


x
sec x dx = ln | sec x + tan x| = 2 tanh1 tan
2

(91)

Z
(92)

Z
(93)

sec3 x dx =

sec2 ax dx =

1
tan ax
a

1
1
sec x tan x + ln | sec x + tan x|
2
2

Z
(94)

## sec x tan x dx = sec x

Z
(95)

Z
(96)

Z
(97)

sec2 x tan x dx =

secn x tan x dx =

1
sec2 x
2

1
secn x, n 6= 0
n

x

csc x dx = ln tan = ln | csc x cot x| + C
2
10

Z
(98)

Z
(99)

1
csc2 ax dx = cot ax
a

1
1
csc3 x dx = cot x csc x + ln | csc x cot x|
2
2
Z

(100)

1
cscn x cot x dx = cscn x, n 6= 0
n
Z
sec x csc x dx = ln | tan x|

(101)

Z
(102)

## x cos x dx = cos x + x sin x

Z
(103)

x cos ax dx =

Z
(104)

Z
(105)

Z
(106)

1
x
cos ax + sin ax
2
a
a


x2 cos x dx = 2x cos x + x2 2 sin x

x2 cos ax dx =

2x cos ax a2 x2 2
+
sin ax
a2
a3

1
xn cos xdx = (i)n+1 [(n + 1, ix) + (1)n (n + 1, ix)]
2
11

Z
(107)

1
xn cos ax dx = (ia)1n [(1)n (n + 1, iax) (n + 1, ixa)]
2
Z
x sin x dx = x cos x + sin x

(108)

Z
x sin ax dx =

(109)

Z
(110)

Z
(112)

(113)

Z
(114)

x cos2 x dx =

1
x2 1
+ cos 2x + x sin 2x
4
8
4

x sin2 x dx =

x2 1
1
cos 2x x sin 2x
4
8
4

x tan2 x dx =

Z
(116)

2x sin ax
2 a2 x 2
cos ax +
3
a
a2

1
xn sin x dx = (i)n [(n + 1, ix) (1)n (n + 1, ix)]
2
Z

(115)


x2 sin x dx = 2 x2 cos x + 2x sin x

x2 sin ax dx =

(111)

x cos ax sin ax
+
a
a2

x2
+ ln cos x + x tan x
2

12

## Products of Trigonometric Functions and Exponentials

Z
(117)

Z
(118)

ebx sin ax dx =

Z
(119)

Z
(120)

a2

1
ebx (b sin ax a cos ax)
+ b2

1
ex cos x dx = ex (sin x + cos x)
2

ebx cos ax dx =

a2

1
ebx (a sin ax + b cos ax)
+ b2

1
xex sin x dx = ex (cos x x cos x + x sin x)
2

1
xex cos x dx = ex (x cos x sin x + x sin x)
2

(121)

(122)

1
ex sin x dx = ex (sin x cos x)
2

## Integrals of Hyperbolic Functions

Z
(123)

cosh ax dx =

Z
(124)

ax
e

2
[a cosh bx b sinh bx] a 6= b
2
eax cosh bx dx = a2ax b

e + x
a=b
4a
2
Z

(125)

1
sinh ax
a

sinh ax dx =
13

1
cosh ax
a

Z
(126)

(127)

ax
e

2
[b cosh bx + a sinh bx] a 6= b
2
ax
e sinh bx dx = a2ax b

e x
a=b
4a
2
Z
1
tanh ax dx = ln cosh ax
a

(a+2b)x
h
i
e
a
a

2bx

F
1
+
,
1,
2
+
,
e
2
1

Z
2b
(a + 2b)
h 2b a
i
1
a
ax
ax
2bx
(128)
e tanh bx dx =
e 2 F1 1, , 1 + , e
a 6= b

a 1 ax 2b
2b

ax

e 2 tan [e ]
a=b
a
Z
1
[a sin ax cosh bx + b cos ax sinh bx]
(129)
cos ax cosh bx dx = 2
a + b2
Z
(130)

cos ax sinh bx dx =

a2

Z
(131)

sin ax cosh bx dx =

a2

1
[a cos ax cosh bx + b sin ax sinh bx]
+ b2

Z
(132)

sin ax sinh bx dx =

1
[b cos ax cosh bx + a sin ax sinh bx]
+ b2

a2

1
[b cosh bx sin ax a cos ax sinh bx]
+ b2

Z
(133)

## sinh ax cosh axdx =

Z

(134)

sinh ax cosh bx dx =

b2

1
[2ax + sinh 2ax]
4a

1
[b cosh bx sinh ax a cosh ax sinh bx]
a2

c 2014. From http://integral-table.com, last revised June 14, 2014. This mate
rial is provided as is without warranty or representation about the accuracy, correctness or